A story of ambition in 50 hoaxes : from the trojan horse to fake tech support - Eaton, Gale (New Delhi : W W norton & company, 2019)
Gale Eaton's "A Story of Ambition in 50 Hoaxes" is a fascinating exploration of human deception throughout history. This book delves into a captivating array of hoaxes, ranging from the ancient Trojan Horse to modern-day tech support scams. Eaton masterfully unravels the motivations behind these deceptions, revealing the intricate web of ambition, greed, and psychological manipulation that drives them. Through a clear and engaging narrative, the author highlights the enduring allure of the hoax, demonstrating how it can both shape and distort our understanding of the world. From historical events to contemporary scams, Eaton's work offers a thought-provoking examination of the human condition, reminding us to remain vigilant against the persuasive power of deception.
Keywords: Personal gain and financial fraud; Power and influence; Exploration and discovery; Fame and celebrity